Urban Desire, Consumer Culture, And Moral Ambiguity in Theodore Dreiser’s Sister Carrie - Soybnazarov Navruzbek Mashrabboy o‘g‘li (International Journal Of Literature And Languages, 2026)
This article reads Sister Carrie as a major naturalist novel in which moral experience is shaped by urban modernity, consumer desire, and social inequality. Drawing on close textual analysis and Yoshinobu Hakutani’s interpretation of Dreiser’s naturalism, the study argues that the novel should not be reduced either to a conventional narrative of female moral decline or to a rigidly deterministic account of human behavior. Instead, Dreiser presents Carrie Meeber as a subject whose desires, decisions, and social mobility emerge within a field structured by economic precarity, class aspiration, spectacle, and chance. Chicago functions not merely as a background but as an active social force that organizes perception, intensifies desire, and narrows the range of viable moral choices. The article further shows that Dreiser complicates mechanistic naturalism by emphasizing the unstable interaction of instinct, circumstance, and partial volition. In this way, Sister Carrie transforms moral decline from a purely personal failing into a socially mediated condition of modern life. The study concludes that the novel remains significant because it redefines moral conflict through the interaction of environment, consumption, and limited agency.